Processes of magmatic differentiation within the southern British and Irish Palaeogene Igneous Province - Meade, Fiona C. (Trinity College (Dublin, Ireland). Department of Geology, 2009)
This thesis presents a geochemical study of magma - crust interaction within the volcanic centres of the southern British and Irish Palaeogene Igneous Province. Three centres occur in northeast Ireland; the Carlingford Igneous Centre, Co. Louth, the Slieve Gullion Igneous Centre, Co. Armagh and the Moume Intrusive Centre, Co. Down; while the fourth, the Drumadoon Intrusive Complex, is on the Isle of Arran, south-west Scotland. Major and trace elements, and Sr, Nd and Pb isotope ratios of both igneous and crustal samples were analysed with the aim of revealing both the extent of magma-crust interaction and processes by which it has occurred. These data allowed the path of the magmas to be traced through the crust and to gauge the processes occurring at various stages during magma storage and ascent, including magma mixing, assimilation during fractional crystallisation and contamination by crustal melts.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin